Two new Phoretomorphic Siteroptes from Galleries of the Southern Pine Beetle (Acarina: Pyemotidae). - Smiley, Robert L.; Moser, John C. (Contributions to Entomology = Beiträge zur Entomologie, 1976)
Two new phoretomorphic species, Siteroptes fusarii and S. trichoderma are discribed. The genera Pediculaster Vitzthum, 1931 and Pygmephorellus Groos & Moser, 1971, are synonymized unter the earlier name Siteroptes Amerling, 1861, because the first two names are based on Phoretomorphic forms of species described in Siteroptes. Specimens of the two new species were reared in laboratory culture by the U.S. Forest Service, Pineville, Louisiana. It was discovered that there were two different distinct female forms for each species and are not separate generic taxa as previously assigned.Nomenclatural Actsfusarii Smiley & Moser, 1976 (Siteroptes), spec. n.trichoderma Smiley & Moser, 1976 (Siteroptes), spec. n.